ALIH FUNGSI LAHAN MENJADI PERKEBUNAN KELAPA SAWIT DAN PERUBAHAN SOSIAL MASYARAKAT LOKAL (Studi Kasus Masyarakat Desa Murutuwu, Kabupaten Barito Timur, Kalimantan Tengah) - Debby Aulia Firdaus; Emmy Sri Mahreda; Wahyu Wahyu; Emmy Lilimantik (EnviroScienteae, 2022)
This study aims to examine the processes and factors behind the conversion of land into oil palm plantation and to analyze land-use changes that affects to environmental, economic, and socio-cultural changes in local community. This research was conducted in Murutuwu Village, East Barito Regency, Central Kalimantan. This study used a qualitative approach. The number of informants as a sampel was 33 people who were determined purposively. The criteria for informants were people who clearly knew the development of the Murutuwu Village area or local communites and/or rubber farmers who transferred land ownership to become oil palm plantation. The result showed that the process of land conversion in Murutuwu Village started from 2007-2008 which was marked by the presence of oil palm plantation investors and the issuance of plantation location permits in 2009 by the local government. The community-owned rubber plantations were then converted into plantations and the construction of an oil palm processing factory. Factors that caused land-use change were externally due to government intervention and intervention from the private sector (companies), and internally due to the high flow of land sales by the community.  The impact of land conversion into oil palm plantations has caused social changes which are characterized by: 1) changes in the environment, either directly (biophysical), or indirectly (demographic), 2) changes in the local community's economy including shifts and diversification of livelihoods as well as changes in income, and 3) there are socio-cultural changes in the local community including the loss of community identity as farmers,the occurrence of social competition, the erosion of community cultural values, and reduced mutual cooperation activities in the community.